RASISME DALAM ISLAM (Peran Bilal bin Rabbah dalam Sejarah Peradapan Islam) - Moch Faizin Muflich (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
In relation to the history of Islamic civilization, the Qur'an is a book that is used as a guide for Muslims where in it are the main teachings that are used as human guidance, especially Muslims when living life. The concept of racism in Islam is a crime that cannot be justified. The crime of racism is an act of racial harassment that occurs to a person or group using discriminatory speech, behavior or acts of violence to show racial intolerance to skin color, descent, culture, language or religion. The prohibition of acts of racism is explained in Surah al Hujurat verse 11. Bilal bin Rabbah is a human who is described as a black person from a family who is destined to become a slave in the Jahilliyah era who has a stand in defending his belief in Islam, the Muezzin of the Prophet who previously only a young slave who was tortured by his master (Umayah bin Khalaf) because it was known that he converted to Islam.